Analisis Kelayakan Pengembangan Konveksi Pakaian Brand Fesyen “Kugle” - M Aldi Gofarizkia; Eli Mas’idah (Jurnal Riset Multidisiplin Edukasi, 2025)
The fashion brand “Kugle” faces significant operational challenges due to its dependence on third-party vendors, which has led to production delays, inconsistent quality, and high operating costs. To address these issues and support sustainable business growth, this study focuses on analyzing the feasibility of establishing an independent convection production facility in the form of equipment for producing t-shirts and pants. The research hypothesis is that the development of an internal production system will be an effective solution to improve quality control, time and cost efficiency, and build a stronger business foundation. This study uses a descriptive qualitative approach with a comprehensive business feasibility study analysis method. The data collection process involved a study of internal company documents, sales data analysis, interviews, and observations. The collected data was then processed and analysed based on six main aspects: market, technical, financial, legal, environmental, and management. Each aspect was evaluated to identify strengths, weaknesses, and potential risks, as well as to validate the proposed hypothesis. The analysis shows that the plan to establish this independent production facility is highly feasible from all aspects. From a market perspective, research has proven that there is strong demand, as well as the feasibility of the project based on STP (Segmentation, Targeting, Positioning) and 4P (Product, Price, Place, Promotion) analyses. Furthermore, from a technical perspective, this model will provide full control over the production process, which will directly resolve issues of quality and delays. Financially, this project is proven to be highly profitable with a positive NPV, an exceptionally high IRR (105%), and a very short Payback Period. From a legal perspective, the readiness in terms of business legality shows a strong foundation, while the environmental aspect shows adequate commitment to managing the impact of production responsibly. Finally, the management aspect shows readiness in managing more complex operations. Therefore, this research hypothesis has been proven, and the establishment of an independent production facility is recommended as a strategic step to transform “Kugle” into a more efficient and competitive brand.